Incorporation of Al3+ on the rectification properties of ADC thin films. Issue 2 (March 2015) - Suresh, R.; Ponnuswamy, V.; Mariappan, R.
Abstract: Highly uniform and well-dispersed ADC (Aluminum doped ceria) films are successfully deposited by NSP technique using cerium nitrate and aluminum nitrate. Effect of Al concentration on the crystallite growth of cerium oxide films is investigated by PL, XRD, FTIR, SEM, AFM UV–vis and I – V studies. Cubic fluorite crystallites are detected by X-ray diffraction pattern with preferred orientation along (1 1 1) direction. Al concentration affects the crysrallinity and structural parameters like grain size, texture coefficient, lattice constant and dislocation density. The change in lattice parameter in doped samples is directly related to the ionic size of the dopants. Because of the smaller size of the dopants, there should be considerable decrease in the lattice parameter of the CeO2 lattice. The transmittance decreases with increasing Al concentration upto 20% and then decreases due to the presence of covalent bonds between cerium and oxygen or the increase in scattering of photon by crystal defects created by doping or due to the increase in the metal to oxygen ratio and lower ionic size of Al. PL spectra revealed that strong and broad emission band is observed at 425 and 469 nm due to the presence of blue and green shift in the visible region. Large agglomerated ring and hollow spherical crystallites are obtained with the typical size in the range 40–68 nm. I – V characteristics show the rectifying nature of this hetero-junction with a typical forward to reverse current ratio of ~7 in the range −4 to +4 V. The turn-on voltage of the hetero-junction is found to be ~2.1 V. The high values in the ideality factor are caused possibly by various effects such as inhomogeneities of inorganic film thickness, nonuniformity of the interfacial charges and the effect of the series resistance ( R s ).